Workshop Menumbuhkan Minat Baca dan Penanganan Kesulitan Membaca Anak di Perumahan Graha Indah Samarinda - Hikmah, Nurul (LPPPM STAI Darul Hikmah Bangkalan, 2021)
In this global era, the world of education is increasingly advanced and developing. Education is one of the references for assessing a country. A country can be said to be developing if it is seen from the education index and the number of illiterates of a country. Humans must adopt a culture of reading. By using the senses of sight and hearing, humans can get the information contained in the objects they